Espécies de capim arroz submetidas às diferentes doses de herbicidas, condições de umidade do solo e adubação nitrogenada - Trivisiol, Vinicius Severo (2020)
Ecotype by Barnyardgrass plants are of great importance in the irrigated rice scenario, being one of the main weeds of the crop, however, began the occurrence of this weed in soybean and corn areas whose soil type is dry. Thus, the present study aimed to verify the morphophysiological responses and herbicide resistance in two barnyardgrass species, one from soybean cultivation areas (Echinochloa crusgalli var. mitis) and the other from irrigated rice cultivation areas (Echinocholoa colona), submitted to different doses of herbicides, soil moisture conditions and nitrogen fertilization. The studies were conducted in a greenhouse using polyethylene vessels for both morphophysiological studies (experiment I) and to evaluate superoxide dismutase production (SOD, POD and Peroxidation) (experiment II) and resistance of the highland population (experiment III, IV, V). Experiment I was a 2x3 factorial, organized in a completely randomized design (DIC), combining barnyardgrass species with three soil moisture levels: shallow water table: 50 % water retention capacity of soil (WRC) and 100% of soil WRC. Experiment II was a 4x2x3 factorial, conducted in DIC, with four doses of nitrogen fertilization: no nitrogen (0 kg N per ha-1), half nitrogen dose (40 kg N per ha-1), nitrogen dose (80 kg N per ha-1) and double nitrogen dose (160 kg N per ha-1), two lowland and highland species and three soil moisture levels (water depth, 100% of soil WRC and 50% of soil WRC). Experiment III, IV and V, conducted in DIC, presented a 4x6x2 factorial, combining nitrogen fertilization doses (0, 40, 80 and 160 kg N-1) with increasing herbicide doses (zero; 50%; registration dose; two, four and eight times herbicide registration dose) and two soil moisture conditions (100% and water depth). It can be observed that the humidity conditions cause morphophysiological changes in the species of barnyardgrass, water depth and 50% of retention capacity, significantly reduce the morphological variables, such as stalk thickness, length and width of the flag leaf, tillering, number of panicles, and dry mass of the plant. The use of nitrogen facilitates the control of rice grass and increases the drying rate of the tested herbicides. Hydrogen peroxide decreased with the increase of nitrogen fertilization for the conditions of 100% CRA and water depth. For the POD enzyme it was not influenced by the humidity conditions and nitrogen doses.